The ethnobotanical character of the Polish Dictionary of Folk Stereotypes and Symbols - Kielak, Olga (Ethnobotany Research and Applications, 2020)
Background: The aim of the article is to present the ethnolinguistic methodology used by a team of Lublin-based ethnolinguists centered around Jerzy Bartmiński, the originator and ed of Słownik stereotypów i symboli ludowych [Dictionary of Folk Stereotypes and Symbols], which has been published since the 1980s, and to demonstrate the ethnobotanic character of the second volume of the Lublin ethnolinguistic dictionary. By outlining the areas common to ethnobotany and ethnolinguistics, the article hopes to pave a way for a satisfactory cooperation between the representatives of both fields. Methods: Using the methodology applied in the abovementioned ethnolinguistic dictionary, in particular the cognitive deﬁnition method, the author reconstructs the dictionary entry mirt ‘myrtle’ (Myrtus communis). On the basis of the collected source material (lexicographic, folklore and ethnographic data), the following semantic subcategories in the cognitive definition of the myrtle are distinguished: complexes, collections and equivalents; appearance and properties; location; cultivation and care; practical, ritualistic, magical and medicinal applications; prophecies; fortune-telling and symbolism, which follow the analysis of names and ways of categorising plants, according to the postulate of the subjective reconstruction of the linguistic worldview. Results: The author presents a tabular compilation of selected semantic subcategories, which are used in Słownik stereotypów i symboli ludowych to describe plants and explains how they are understood. As a result, the proposed facets can inspire other similar research in Europe or worldwide. Conclusion: On the basis of the conducted analyses, the author comes to the conclusion that the issues described in particular facets, which constitute the ethnolinguistic narrative about plants largely coincide with the area of interest of ethnobotany. The commonalities between both disciplines include: the object of research, the relations between the plant world and the human world described in both disciplines, the appreciation of the role of language and the subjective view of the world. The reflections presented in this article indicate the possibility of future interdisciplinary research, bringing together linguists and botanists. Keywords: ethnolinguistics, ethnobotany, cognitive definition, linguistic worldview